Acute Respiratory Distress and Its Risk Factors among Neonates Admitted in a Tertiary Care Center of Western Nepal - Adhikari, Jyoti; Aryal, Sajju; Gupta, Veena (Journal of Nepalgunj Medical College, 2017)
Background: Neonatal period is defined as a period from birth to under 4 weeks (